The Relationship between Arm Muscle Strength and Togok Flexibility with Butterfly Swimming Speed - Sariul, Sariul; Jud; Suhartiwi; Marsuna; Mastang (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
The purpose of this study was to determine how the arm muscle strength and trunk flexibility of Kendari City swimmers relate to their butterfly swimming speed. The descriptive correlational research category covers this work. The study population consisted of 35 swimmers from Kendari City, 30 of whom were male and 5 of whom were female. Thirty male swimmers from Kendari City were the sample for this study because the sampling method was applied by utilizing the overall sampling strategy, which uses the population as a sample. Static flexibility tests were used to assess trunk and neck flexibility, butterfly swimming tests were used to measure butterfly swimming speed, and grip strength tests were used to measure arm muscle strength. The mean, standard deviation, mean, media, maximum value, and minimum value were all calculated as part of the descriptive analysis. Using SPSS 26, conduct regression analysis of normality, linearity, and correlation tests. Based on the results of data analysis, arm muscle strength and body flexibility of Kendari City swimming athletes correlate significantly with butterfly swimming speed (rx1,2.y = 0.669 > r(0.05)(30) = 0.361). Based on the results of data analysis, it can be concluded that there is a significant relationship between arm muscle strength and trunk flexibility with butterfly swimming speed in Kendari City swimming athletes.